Fault‐tolerant quantum implementation of conventional decoder logic with enable input - Laxmidhar Biswal; Bappaditya Mondal; Hafizur Rahaman (IET Circuits, Devices and Systems, 2021)
Abstract Decoherence is the greatest obstacle to the physical realization of scalable quantum computer, jeopardises coherent superposition of the qubit, and makes qubit extremely fragile. Quantum Error Correction Code (QECC), and Fault‐tolerant quantum computation collectively could protect qubit and improve scalability. On the other hand, the conventional logic circuit is no more useful in quantum computing due to much difference from quantum logic. However, quantum computer has to perform classical tasks which can be addressed by translating to its equivalent quantum algorithm. Herein, zero‐garbage‐based reversible and fault‐tolerant quantum circuit for 1 : 2, and 2 : 4 Decoder with enable signal using Clifford + T‐group are proposed. Further, the design approach to implement n : 2n decoder on fault‐tolerant quantum logic in linear T − depth is extended. Besides, performance parameters likely T − count, T − depth, and garbage output have been evaluated for n : 2n decoder.